Public Financial Management and Fiscal Outcomes in Sub-Saharan African Heavily-Indebted Poor Countries - Cabezon, Ezequiel (IMF Working Papers; Working Paper ;, 2008)
This paper examines, in a formal econometric framework, the linkages between public financial management and fiscal outcomes in sub-Saharan African countries. Similar analyses have been done for Latin America, Europe, and the United States, but none in the context of low-income countries. Using public financial management indicators, as measured in two recent assessments related to the Heavily-Indebted Poor Countries Initiative, this study shows that improving public financial management leads to better fiscal outcomes, as measured by the overall fiscal balance and external debt levels, after controlling for other characteristics that might alter fiscal outcomes.